Until the end of the ninth - Bollinger, Beth Mary (AuthorHouse, 2006)
There are moments in baseball that sparkle with magic. And moments that break our hearts. And then there was the moment in 1946 when one minor league baseball team's hope for magical moments came crashing to a fiery end. That season began like seasons begin, except this time even more sweetly. It was the first season right after World War II, with men returning from foxholes to dugouts, back to a game that had been put on hold, back to their dreams of the Big Leagues. Some of those men found their way to Spokane, Washington to play for the minor league club there. They were special men. They knew how to be a team and they knew how to win, especially in the waning moments of the ninth, when all that seemed lost could be won if they just imagined it. They knew how to play ball as it was meant to be played. What they did not know was how to die too young. That, they had to learn. What if the earth knew that something was about to happen and tried to prepare for it by calling to it a soul for help? A soul with a joyful heart, whose story paralleled the story of these men ... who knew, as they did, what it meant to be in a war, to watch a friend die, to strive in every moment even as the moments waned, to believe in a destiny, to feel its arrival ... who knew, as they would, how to die too young, by fire, as destiny arrived.